2019
DOI: 10.4068/cmj.2019.55.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Real World Comparison of Rivaroxaban and Warfarin in Korean Patients with Atrial Fibrillation: Propensity Matching Cohort Analysis

Abstract: Rivaroxaban has emerged as a potential alternative to warfarin for the prevention of thromboembolism in patients with atrial fibrillation (AF). However, there has been concern for the risk of major bleeding, especially in Asian patients. We investigated the efficacy and safety of rivaroxaban compared to warfarin in Korean real world practice. A total of 2,208 consecutive non-valvular AF patients were divided into the Warfarin group (n=990) and the Rivaroxaban group (n=1218). Propensity matched 1-year clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…46 full-text articles were obtained for further assessment of eligibility, and 34 articles were excluded for reasons listed in Supplementary Table S3 . Finally, 12 studies ( Kohsaka et al, 2017 ; Chan et al, 2018 ; Cho et al, 2018 ; Huang et al, 2018 ; Lai et al, 2018 ; Lee et al, 2018 ; Okumura et al, 2018 ; Chan et al, 2019 ; Jeong et al, 2019 ; Lee et al, 2019 ; Cho et al, 2020 ; Kohsaka et al, 2020 ) involving 292,815 Asian patients with AF were included, with 169,383 patients using rivaroxaban and 123,432 patients using warfarin. Among them, eight studies with on-label low-dose rivaroxaban were conducted in Japan (3 studies) and Taiwan (5 studies), and four studies with off-label low-dose rivaroxaban were implemented in Korea ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 full-text articles were obtained for further assessment of eligibility, and 34 articles were excluded for reasons listed in Supplementary Table S3 . Finally, 12 studies ( Kohsaka et al, 2017 ; Chan et al, 2018 ; Cho et al, 2018 ; Huang et al, 2018 ; Lai et al, 2018 ; Lee et al, 2018 ; Okumura et al, 2018 ; Chan et al, 2019 ; Jeong et al, 2019 ; Lee et al, 2019 ; Cho et al, 2020 ; Kohsaka et al, 2020 ) involving 292,815 Asian patients with AF were included, with 169,383 patients using rivaroxaban and 123,432 patients using warfarin. Among them, eight studies with on-label low-dose rivaroxaban were conducted in Japan (3 studies) and Taiwan (5 studies), and four studies with off-label low-dose rivaroxaban were implemented in Korea ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another United States national prospective registry study indicated that low-dose DOACs were associated with an obvious increase in mortality ( Steinberg et al, 2016 ). In recent years, many more contemporary real-world studies that focused on low-dose rivaroxaban in Asian have been published ( Kohsaka et al, 2017 ; Chan et al, 2018 ; Cho et al, 2018 ; Huang et al, 2018 ; Lai et al, 2018 ; Lee et al, 2018 ; Okumura et al, 2018 ; Chan et al, 2019 ; Jeong et al, 2019 ; Lee et al, 2019 ; Cho et al, 2020 ; Kohsaka et al, 2020 ). It is well-known that real-world studies by integrating data from electronic health records (EHRs), claims databases, and disease registries could extend findings of RCTs to large patient populations in real-world practice.…”
Section: Discussionmentioning
confidence: 99%
“…Then sixty-four articles without GIB data or using inappropriate statistical methods were ruled out. Fifteen articles probably extracted from the identical database or the same population were not applied [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Sixteen articles investigating non-Asians or not fully Asians were not enrolled [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 18 included studies were conducted in China, 12,13,15,18,26 28 Singapore, 12,15,19 Korea, 12 15,17 –19,29 Japan, 12,13,15,30,31 India 12 , Malaysia, 11,12,15,16,32 the Philippines, 12,15 Turkey, 33 Israel, 34 or Thailand. 12 A total of 71 227 anticoagulated patients with NVAF were studied.…”
Section: Resultsmentioning
confidence: 99%